2022
DOI: 10.3390/ijerph20010611
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Foreign Language Enjoyment through Online Cooperative Learning: A Longitudinal Study of EFL Learners

Abstract: This study examines university students’ foreign language enjoyment (FLE) in an online cooperative learning (CL) context and explores, taking a positive psychology approach, how and why CL may shape FLE. To this end, 98 Chinese university students studying English as a foreign language (EFL) were assigned into experimental (n = 49) and control groups (n = 49). Both groups completed a short-form foreign language enjoyment (FLE) scale before and after a 3-month intervention. The students in the experimental grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 78 publications
(126 reference statements)
1
9
0
Order By: Relevance
“…The quantitative findings indicate that peer support in digital foreign language classes can bolster students' enjoyment and confidence while also exacerbating anxiety. This aligns with prior research demonstrating peer interaction has mixed implications for foreign language learning (Chen et al, 2022;Zheng and Zhou, 2023). Self-efficacy appears to serve as a mechanism through which peer support influences affective experiences, supporting previous research (Mastrocola and Flynn, 2017).…”
Section: Integration Of Quantitative and Qualitative Findingssupporting
confidence: 87%
“…The quantitative findings indicate that peer support in digital foreign language classes can bolster students' enjoyment and confidence while also exacerbating anxiety. This aligns with prior research demonstrating peer interaction has mixed implications for foreign language learning (Chen et al, 2022;Zheng and Zhou, 2023). Self-efficacy appears to serve as a mechanism through which peer support influences affective experiences, supporting previous research (Mastrocola and Flynn, 2017).…”
Section: Integration Of Quantitative and Qualitative Findingssupporting
confidence: 87%
“…The initial results also allow us to agree with Stravers' idea (2022) that enjoying learning a foreign language increases students' willingness and participation in communicative activities, consequently improving their oral skills. Consistent with this, several studies have shown that a high level of enjoyment is directly associated with a greater willingness to communicate in a second language (Alsaraireh, 2022;Mohammad et al, 2022;Aldosari et al, 2023;Yung and Chiu, 2023;Zheng and Zhou, 2023). When students enjoy the learning process and feel motivated and enthusiastic, they are more willing to actively participate in oral interactions actively, enhancing their communication skills and oral proficiency.…”
Section: Discussionmentioning
confidence: 65%
“…Research on enjoyment in diverse educational contexts is emerging as a central theme in the literature, emphasizing the need to measure students' positive emotional experiences during language learning (Dewaele and Alfawzan, 2018). In that regard, investigations into EFL enjoyment have yielded positive outcomes, as students not only encounter positive emotions but also cultivate competencies (Zheng and Zhou, 2023).…”
Section: The Enjoyment and Eflmentioning
confidence: 99%
“…Therefore, in order to realize high-quality learning, it is equally important to come up with a learning strategy that best suits the student's condition, learning style, and comfort in learning. One study revealed that students who have a pleasant cooperative experience during online learning, usually have a high sense of foreign language enjoyment, give satisfactory marks to their performance, and feel confident in their ability to achieve better foreign language performance in the future (Clifford & Reisinger, 2019;Zheng & Zhou, 2023). According to Oxford (1990), it is common for students to develop their own study strategies as a means of enhancing their academic performance.…”
Section: Introductionmentioning
confidence: 99%